2016
DOI: 10.1128/jmbe.v17i3.1123
|View full text |Cite
|
Sign up to set email alerts
|

Video Lecture Capture Technology Helps Students Study without Affecting Attendance in Large Microbiology Lecture Courses

Abstract: Recording lectures using video lecture capture software and making them available for students to watch anytime, from anywhere, has become a common practice in many universities across many disciplines. The software has become increasingly easy to use and is commonly provided and maintained by higher education institutions. Several studies have reported that students use lecture capture to enhance their learning and study for assessments, as well as to catch up on material they miss when they cannot attend cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Similarly, according to Marchand et al (2014) , students believed that lecture capture would not affect their attendance but instructors noted increased absenteeism. Nevertheless, several works also reported non-significant relations between lecture capture and attendance ( Baker et al, 2018 ; Bollmeier et al, 2010 ; Davis et al, 2009 ; Franklin et al, 2011 ; Groen et al, 2016 ; Gysbers et al, 2011; McLean & Suchman, 2016 ; Nordmann et al, 2019 ; Shaw & Molnar, 2011 ; von Konsky et al, 2009 ; Wiese and Newton, 2013 ; Williams et al, 2016 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Similarly, according to Marchand et al (2014) , students believed that lecture capture would not affect their attendance but instructors noted increased absenteeism. Nevertheless, several works also reported non-significant relations between lecture capture and attendance ( Baker et al, 2018 ; Bollmeier et al, 2010 ; Davis et al, 2009 ; Franklin et al, 2011 ; Groen et al, 2016 ; Gysbers et al, 2011; McLean & Suchman, 2016 ; Nordmann et al, 2019 ; Shaw & Molnar, 2011 ; von Konsky et al, 2009 ; Wiese and Newton, 2013 ; Williams et al, 2016 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…If a student fails to attend more than 25% of classes for a specific course within one semester, the student will receive a failing grade for that course, thus ensuring optimal student attendance. A multitude of studies have been conducted in this regard and many studies have concluded that lecture capture does not affect student attendance, whereby students use the recordings to supplement or enhance lecture material rather than replace live lectures (McLean & Suchman, 2016;Copley, 2007;Traphagan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effect of lecture capture on attendance have shown conflicting results. Although several studies found no or only small effects [24,34,35], others reported a substantial drop in lecture attendance when lecture capture was introduced [12,[36][37][38].…”
mentioning
confidence: 99%